Pembentukan Akhlak Siswa melalui kegiatan Halaqah Al-Qur’an di SMK Islam Al-Amal Surabaya - Trisna Febi Nurlaili (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the importance of fostering students’ moral character within the school environment through religious activities, one of which is the Qur’an halaqah. The purpose of this study is to examine the implementation of the Qur’an halaqah activities and their role in shaping students’ character at SMK Islam Al-Amal Surabaya. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that the regular implementation of Qur’an halaqah activities is able to provide a positive impact on students’ character, such as improving discipline, politeness, and responsibility. The habituation process carried out in these activities becomes a key factor in shaping students’ behavior. The implications of this study suggest that the Qur’an halaqah can serve as an effective program for developing students’ moral character in schools; therefore, it should be maintained and continuously developed.